A Study on the Modernity of Rural Residential Architecture in Fars Province - khosro Movahed (مسکن و محیط روستا, 2015)
Today, we are faced with a variety of rural residential architecture with significant differences with their precursors . Studies show that, in the past fifty years, modernization has caused considerable changes in the architecture of rural housing in Fars province. These changes have transformed village features and have caused different problems in rural areas.